Women and labour in late colonial India : the Bengal jute industry - Sen, Samita (Cambridge studies in Indian history and society, 1999)
In a history of labouring women in Calcutta, the author demonstrates how social constructions of gender shaped their lives and how the long-term trends in the Indian economy devalued their labour. The study makes a significant contribution to the social and economic history of colonial India.